PERANAN NILAI-NILAI DASAR KEAGAMAAN TERHADAP PEMBINAAN KARAKTER PESERTA DIDIK DI SMK NEGERI 2 KOTA PAREPARE - Muzakkir M (IAIN PAREPARE, 2016)
Implementation of education in religious character building becomes the main problem in learning in the school environment today. The impelementative offer through the development of educational psychology approach becomes an integral part that must be socialized. This writing uses a qualitative descriptive type through educational psychologyapproach that is supported with the relevant educational approach. The basic values of religion to build the character of learners in SMK Negeri 2 Parepare is applied with the pattern of formation of participatory policy model for educational purpose, put forward the function of policy authority persuasively to the school stakeholder in performing character building pattern based on the rule of character education program. The strategy applied is a character-based, culture-based and community-based character education model. The pattern of character building of learners through educational psychology approach maximizes the pattern of tazkiyah based religious education development on the learner's soul, runs a coaching pattern appropriate to the situation and condition of the school, educators and learners. Character building of learners through educational psychology approach implemented or developed with the increase of worship; Giving advice, noble touch, supervision and control activities, and guidance targib and tarhib.